Sequencing of Dna Isolated From Colorectal Sample Fixed in Liquid Formalin : Obstacles and Required Modifications (Dhaka University Journal of Biological Sciences, 2020)
The necessary modifications in the protocol of general purpose DNA isolation kit to isolate and amplify a target region of genome from colorectal cancer tissues fixed in liquid formalin were made. It is shown that a one hour digestion with proteinase K yields enough DNA from formalin fixed colorectal tissue for subsequent PCR and sequencing. Moreover, using 100% ethanol instead of standard 50% during DNA binding step in the column improves the yield. As DNA fragmentation is unavoidable in formalin fixed tissue, PCR protocol was modified by increasing polymerase concentration to get successful amplification. Following these modifications, two regions of KRAS and BRAF genes were amplified and successfully sequenced from three different patients. These modifications provide a low cost option for Sanger sequencing of DNA isolated from formalin fixed tissue.Dhaka Univ. J. Biol. Sci. 29(2): 165-174, 2020 (July)